The pragmatics and Semiotics Analysis of Vinyl Record Cover Art They Fell From The Sky's Album DECADE - Yudhanto, Sigied Himawan; Risdianto, Faizal (Journal of Pragmatics Research, 2022)
In this study, the researchers focus on the meaning of the DECADE album cover from They Fell From The Sky music band. This was chosen because the artwork used is quite attractive and has This study uses qualitative research with a descriptive method. The analysis was carried out using the semiotic theory of Roland Barthes and the pragmatics theory of John Searle. This study aimed to determine the meaning contained in the cover design of the DECADE album. This research shows that between context signs and visible signs, there is a relationship where the two synergize in the title. The band, namely "They Fell From The Sky," by using a skull image that uses an astronaut costume in an iconic, denotative, and connotative symbolizing "death," a form of death because "falling from the sky" so the message to be conveyed is to publish the Decade album which for ten years or "a decade" like struggling until astronauts in outer space experience death as if falling from the sky. The Astronaut's skull artwork entitled in Indonesian "Binasa" ("Perish" in English) which is the basis of the DECADE album cover design, also strengthens this interpretation. Keywords: Album cover, Semiotics, Pragmatics.